Marketing Strategy Through Social Media in Increasing Sales at Zheni Rz Furniture Store East Lampung - Saefudin, Rochmad; Warganegara, Tri Lestira Putri (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
The problem that occurs in Zheni Rz Furniture Store is the lack of marketing through social media, considering the large number of social media users who can be a means to promote as a marketing strategy to face increasingly fierce competition. This study aims to analyze methods that can be used to increase sales at Zheni Rz Furniture Store. Method analysis in research using a qualitative descriptive approach. Where, research does not use quantitative measurements to describe and explain phenomena. This research uses SWOT analysis as a means of qualitative descriptive approach. The results show that Zheni Rz Furniture Store is in quadrant 1 with a very advantageous position because it has strengths and opportunities that can be optimized there. In this quadrant 1, Zheni RZ Furniture store East Lampung can use an aggressive growth policy. The SWOT diagram table shows the strategies that Zheni Rz Furniture Store can use to help increase store sales.